On the R-curve and cohesive law of glass/epoxy end-notch flexure specimens with 0//θ interface fiber angles - M. Salamat-Talab (Elsevier, 2021)
In the current paper, the effects of interface fiber angles on the characteristics of R-curve and the cohesive law shape of end-notch-flexure specimens are investigated using numerical and empirical methods. To this aim, laminated composites manufactured by E-glass/epoxy with 0//θ interface where θ = 0, 15, 45, 60, and 90 were fabricated and tested. The mode II laminated fracture toughness and the cohesive shear traction-separation model were obtained irrespective of the impact of the remote-ply orientation. The empirical results showed that as the interface fiber angle rises, the crack growth behavior in the samples becomes more stable which is evident in the augmented length of the steady-state fracture process zone. Furthermore, the maximum bearable load of specimens drops considerably. Also, the delamination toughness propagation is approximately identical for all specimens. This is the case even if the initiation of delamination toughness is significantly reduced by increasing the interface fiber angle. After parameter identification of the cohesive zone model and conducting numerical analyses, it was demonstrated that this model with the proposed linear-exponential softening behavior can estimate the load-displacement response of samples that display a pronounced R-curve behavior.